[Dissemination of hydrogeology and applied geology: a service to citizens for greater awareness and participation] - Gafa’, Rossella Maria; La Vigna, Francesco; Martarelli , Lucio; Monti, Gennaro Maria; Silvi, Angelantonio; Sanna, Cristina; Mariotti, Silvia (Acque Sotterranee - Italian Journal of Groundwater, 2023)
[Article in Italian]